Enantioselective syntheses and biological studies of aeruginosin 298-A and its analogs: Application of catalytic asymmetric phase-transfer reaction - Fukuta, Yuhei (National Academy of Sciences, 2004)
Aeruginosin 298-A was isolated from the freshwater cyanobacterium Microcystis aeruginosa (NIES-298) and is an equipotent thrombin and trypsin inhibitor. A variety of analogs were synthesized to gain insight into the structure–activity relations. We developed a versatile synthetic process for aeruginosin 298-A as well as several attractive analogs, in which all stereocenters were controlled by catalytic asymmetric phase-transfer reaction promoted by two-center asymmetric catalysts and catalytic asymmetric epoxidation promoted by a lanthanide–BINOL complex. Furthermore, serine protease inhibitory activities of aeruginosin 298-A and its analogs were examined.